IN VIVO and IN VITRO 27AI NMR studies of aluminium(III) chelates of triazacyclononane polycarboxylate ligands - André, João P. (2002)
The metallic radioisotope of a known radiopharmaceutical chelate, 67Ga(NOTA) (NOTA=1,4,7-triazacyclonane-1,4,7-triacetic acid), used for tumor detection, was substituted by the chemically similar but non radioactive aluminum ion. Our aim was to detect and evaluate the in vivo behavior of the chelate. For this purpose, Al(NOTA) and the related chelate Al(NODASA) (NODASA=1,4,7-triazacyclononane-1-succinic acid-4,7-diacetic acid) were studied using in vitro and in vivo 27Al NMR spectroscopy in rats. Both chelates showed high stability towards acid catalyzed dissociation and their 27Al NMR resonances are characteristic of highly symmetrical species, with chemical shifts within the range for octahedral or pseudo-octahedral geometries. The thermodynamic stability constant of the novel chelate Al(NODASA) was estimated using 27Al NMR. The obtained value suggested that the chelate does not undergo in vivo demetalation by transferrin. The in vivo spectroscopic studies and the analysis of blood and urine samples for Al(III) concentrations indicated that the chelates remain intact under physiological conditions and that they are mainly eliminated from the body through the kidneys.